Ponencia como estrategia para desarrollar la expresión oral, área lengua y literatura, séptimo grado, Escuela Alcides Pesantes, Santa Rosa, 2023-2024 - Diaz Llivipuma, Cristian Oswaldo (Machala: Universidad Técnica de Machala, 2024)
The following research work is focused on the collection of updated information about the lecture as a didactic strategy to develop oral expression and promote critical thinking, which responds to a rigorous field study of qualitative-quantitative character. Applying research techniques and methods such as inductive-deductive, descriptive, analytical-synthetic, the instruments used for data collection were the interview and survey, which effectively evidenced the educational reality according to the stated objective. For the development of the research project, we start with the analysis of the object of study, the identification of the central problem and selecting the research objectives, being this to determine the level of oral expression for the development of critical thinking in the students of seventh grade of general basic education of the school Gral. Alcides Pesantes 2023-2024. Consequently, the respective variables to be studied were established, The Presentation and Oral Expression, which were included in the conceptual theoretical framework. The research is based on the use of scientific bibliographic sources, that is, indexed and updated articles and documents with the objective of reinforcing the indicators selected for the theoretical framework, which arises from the variables. The Presentation and Oral Expression; the work is justified in the normative, the normative and the conceptual framework. The research instruments used in the degree work for the collection of degree data correspond to 73 people who represent the universe, which are distributed as follows, 3 teachers, 3 sevenths A-B-C and 70 students distributed as follows, 25 in the A, 22 in the B, 23 in the C. Since the universe is less than 100, a survey was elaborated, 3 seventh (A-B-C) and 70 students distributed as follows, 25 in A, 22 in B, 23 in C. Since the universe is less than 100, a survey was elaborated in its totality. Thanks to the application of the instruments, it is evident that the level of oral expression presented by the students of the selected school is average, which leads to the realization and proposal of the implementation of a manual of didactic strategies to improve the oral expression of seventh grade students, through the implementation of this manual as a methodological alternative. The Manual of didactic strategies presents a high impact due to the novelty of Basic Education, being the first educational resource that links these strategies with education that can be used in the different subjects of education to enhance critical thinking. The final product provides the teacher with feasibility and innovation in his praxis, especially with the implementation of this manual, it seeks to improve the quality of education, responding to the established problems.
El siguiente trabajo de investigación está enfocado en la recolección de información actualizada acerca de la ponencia como estrategia didáctica para desarrollar la expresión oral y promover un pensamiento crítico, la cual responde a un riguroso estudio de campo de carácter cuali-cuantitavo. Aplicando técnicas y métodos de investigación como el inductivo-deductivo, descriptivo, analítico-sintético, los instrumentos utilizados para la recolección de datos fueron la entrevista y encuesta, las cuales evidenciaron con efectividad la realidad educativa en función al objetivo planteado. Para el desarrollo del proyecto de investigación se parte con el análisis del objeto de estudio, la identificación del problema central y seleccionando los objetivos de investigación, siendo esta para determinar el nivel de expresión oral para el desarrollo de pensamiento crítico en los estudiantes de séptimo grado de educación general básica de la escuela Gral. Alcides Pesantes 2023-2024. Por consiguiente, se estableció las respectivas variables por estudiar. La Ponencia y Expresión Oral, las cuales se realizó el marco teórico conceptual. La investigación se encuentra fundamentada por el uso de fuentes bibliográficas de corte científico, es decir, artículos y documentos indexados y actualizados con el objetivo de reforzar los indicadores seleccionados para el marco teórico, el cual surge a partir de las variables. La Ponencia y Expresión Oral, el trabajo se llega a justificar en la normativa legal del Ecuador como son. La Constitución, La Ley Orgánica De Educación Superior LOES. Los instrumentos de investigación empleados en el trabajo de titulación para la recolección de datos de titulación corresponden a 73 personas que representan el Universo, la cual están repartidas de la siguientes manera 3 docentes, 3 séptimos A-B-C y 70 estudiantes distribuidos de la siguiente manera, 25 en al A, 22 en el B, 23 en el C. En virtud que el universo es menor a 100 se elaboró una encuesta en su totalidad. Gracias a la aplicación de los instrumentos se evidencia que el nivel de expresión oral que presentan los estudiantes de la escuela seleccionada es medio, lo que conlleva a la realización y proposición de la implementación de una manual de estrategias didácticas para mejorar la expresión oral de los estudiantes de séptimo grado, a través de la implementación de este manual como una alternativa metodológica. El Manual de estrategias didácticas presenta un alto impacto debido a la novedad de Educación Básica, siendo el primer recurso educativo que vincula estas estrategias con la educación que se pueden emplear en las distintas materias de la educación para potenciar el pensamiento crítico. El producto final le brinda al docente factibilidad e innovador e su praxis, sobre todo con la implementación de dicho manual, busca mejorar la calidad educativa, dando respuesta a la problemática establecida.
Keywords: EXPRESION ORAL; PONENCIA; PENSAMIENTO CRITICO; HABILIDAD LINGUISTICA